Tipe penggunaan lahan memengaruhi keanekaragaman dan komposisi hymenopteran parasitoid di Jambi - Tawakkal, Muhammad Iqbal; Rizali, Akhmad; Larasati, Anik; Sari, Adha; Hidayat, Purnama; Buchori, Damayanti (Perhimpunan Entomologi Indonesia, 2019)
Hymenoptera is one of the four largest insect orders in the world, one of which is its role as a natural enemy (parasitoids, predators). Land conversion can affect the diversity and composition of the parasitoid Hymenoptera and its ecological role. This study aims to examine the effect of land use types on the diversity and composition of hymenopterans parasitoid in Jambi. The study was conducted on various types of land use in the Harapan Forest landscape and Bukit Duabelas National Park (TNBD), Jambi Province including forests, rubber forests, oil palm plantations, and rubber plantations. Insect sampling was conducted from March to September 2013, using fogging techniques. A total of 14,258 hymenopteran parasitoid individuals consisting of 30 families were obtained from all study sites. Encyrtidae, Braconidae, Aphelinidae, Eulophidae, Scelionidae, Ceraphronidae, and Platigasteridae families are found in high abundance. Oil palm land use types are found to have different parasitoid compositions compared to other land use types, while forest and rubber forest land use types have high species composition. The results of this study indicate that the type of land use affects the diversity and composition of hymenopteran parasitoid species.